Infective Endocarditis Caused by Brevibacterium sanguinis and a Review of Literature - Özlem AYDEMİR; Gökçen ORMANOĞLU; İbrahim KOCAYİĞİT; Mehmet Şirin YILDIZ; Mehmet KÖROĞLU (Mediterranean Journal of Infection, Microbes and Antimicrobials)
The Brevibacterium spp. are opportunistic Gram-positive bacilli found in human skin flora and dairy products. Although not generally accepted as human pathogens, the Brevibacterium species are rare causes of infections such as bacteremia, endocarditis, peritonitis, and osteomyelitis, especially in immunosuppressive patients, in recent years. Herein, we aimed to report the first case of infective endocarditis caused by Brevibacterium sanguinis in a patient undergoing hemodialysis for chronic renal failure via an indwelling hemodialysis catheter.